Peran Locus of Control Sebagai Variabel Intervening dalam Pengaruh Pengetahuan Keuangan dan Sikap Keuangan terhadap Perilakui Pengelolaan Keuangan pada UMKM - Islami, Adelia Wahyu; Rahmawati, Ika Yustina; Tubastuvi, Naelati; Haryanto, Totok (Universitas Batanghari, 2024)
This research aims to examine the influence of financial knowledge, financial attitudes, and locus of control as intervening variables on UMKM in the Purwokerto area. The method used in sampling was probability sampling and the number of samples in this study was 100 respondents. Data analysis in this research uses the classical assumption test, multiple linear regression (t test), coefficient of determination and path analysis. The research results show that financial knowledge and financial attitudes directly have a positive and significant effect on locus of control. Financial attitude has a positive and significant effect on financial management behavior, while financial knowledge and locus of control have no effect on financial management behavior. Locus of control is not able to mediate the influence of financial knowledge on financial management behavior and locus of control is able to mediate the influence of financial attitudes on financial management behavior.